Hyperinflammation with COVID-19: The key to patient deterioration?. (October 2020) - Haigh, Kathryn; Syrimi, Zoe Joanna; Irvine, Sharon; Blanchard, Tom J.; Pervaiz, Muhammad Sajid; Toth, Arpad G.; Ratcliffe, Libuse
Abstract: Background: The potential risk of cytokine storm in patients with coronavirus disease 2019 (COVID-19) has been described [1 ]; we write to share our experience treating a 17-year-old male with haemophagocytic lymphohistiocytosis (HLH) secondary to COVID-19 infection. Case report: This patient presented with cough, sore throat, anorexia and pyrexia. On examination, he had gross cervical lymphadenopathy and palpable splenomegaly. Nose and throat swab for SARS-CoV-2 was positive and blood tests revealed pancytopaenia with very high ferritin, triglyceride and d-dimer levels. The patient's H-Score [2 ] was calculated at 220, suggesting probability of HLH of 93–96%. Considering Russell and colleagues' [3 ] comments about potential harm of corticosteroid use in patients with COVID-19 infection, the patient was commenced on treatment with the selective IL-1 receptor antagonist drug, Anakinra, and a two-day course of intravenous immunoglobulin. Results: The patient responded rapidly to treatment, becoming apyrexial after 24 h. His lymph nodes and spleen began to normalise after the first 48 h, at which time point the ferritin also started to decrease. He was discharged after 11 days feeling fit and well. Conclusion: This case certainly illustrates the importance of hyperinflammation syndromes in COVID-19. It also raises the question – is the severe pneumonitis seen in patients with COVID-19 an immunological phenomenon? We know that the viral load of patients with COVID-19 seems to peak in the early stages of illness [4, 5 ]; however, patients deteriorate later in the disease course, at around days 10–14. This patient, who had risk factors for deterioration (male, pancytopaenic), did not develop an oxygen requirement and clinically and biochemically improved rapidly on Anakinra with no adverse events. We might suggest Anakinra to the scientific community as a treatment option in COVID-19 infection. Highlights: Hyperinflammation syndromes should be considered in coronavirus disease 2019. Haemophagocytic lymphohistiocytosis secondary to coronavirus disease 2019 Avoiding steroids and instead using immunologics in coronavirus disease 2019 Using selective IL-1 receptor antagonists for treatment in coronavirus disease 2019